Existence, Uniqueness and Stability of Periodic Solution for Nonlinear System of Integro-Differential Equations - Butris, Raad N.; Rafeeq, Ava Sh.; Faris, Hewa S. (Science Journal of University of Zakho, 2017)
In this paper, we investigate the existence, uniqueness, and stability of the periodic solution for the system of nonlinear integro-differential equations by using the numerical-analytic methods for investigating the solutions and the periodic solutions of ordinary differential equations, which are given by A. Samoilenko.